Pengaruh Faktor Internal dan Faktor Eksternal terhadap Perataan Laba Bank Umum Syariah Indonesia Periode 2014-2018 - Setiawati Indah Gempita; Leni Nur Pratiwi; Rani Putri Kusuma Dewi (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to see the effect of Total Financing (TF), Non Performing Financing (NPF), Earnings Before Taxes and Provision (EBTP), Good Corporate Governance (GCG) proxied by the Audit Committee, Capital Adequacy Ratio (CAR), BI rate. and Inflation on Income Smoothing at Islamic Commercial Banks (BUS) for the period 2014-2018. This research is a quantitative study, the selection was by purposive sampling method. The data used are secondary data. The data analysis method uses panel data regression analysis using the Eviews10 program tool. The data population in this study were 12 Islamic commercial banks in Indonesia which will be sampled in the study. The results of this study indicate that simultaneously internal and external factors have a significant effect on income smoothing. Partially the NPF, EBTP, GCG, CAR variables have a significant effect on income smoothing, while TF, BI rate and the inflation rate do not have a significant effect on income smoothing.